A mediation-moderation model of transformational leadership and intrinsic work motivation for nurturing employee performance - Udin, Udin (Journal of Social Economics Research, 2023)
The main purpose of this study is to examine how transformational leadership encourages intrinsic work motivation, which leads to improved employee performance, as well as to analyze the mediating and moderating role of intrinsic work motivation in the relationship between transformational leadership and employee performance. Research data was collected from employees of a community health center in Riau, Indonesia. A two-step approach to partial least squares structural equation modeling (PLS-SEM) employing SmartPLS 3.0 software was adopted to scrutinize the mediator and moderator variable. The research findings of this study show that transformational leadership significantly affects intrinsic work motivation and employee performance. Furthermore, the findings prove the significant mediating and moderating effect of intrinsic work motivation in the relationship between transformational leadership and employee performance. This study concludes that transformational leadership can enhance employee performance via the interactive influence of intrinsic work motivation by encouraging employees to better understand and enjoy their work, think outside the box, and generate bright ideas that lead to innovative performance within the organization. The findings suggest that the community health center should be developing and applying transformational leadership to stimulate intrinsic work motivation. This would lead to superior employee performance.